Church's documents on the issue of environment - Sgreccia, E.; Pennacchini, M.; Fisso, M. B. (Medicina e Morale, 2000)
This article analyzes all the documents of the pontifical and episcopal Magisterium, along with some by ecclesiastical representatives on the issue of environment. The authors pursue the aim of showing the development. The article highlights the role played by the Catholic Curch in building a new ecological consciousness, underlining how the interest of Catholic Church in the complex ecological problem historically arose along with ecological issue themselves. The authors intend to demonstrate the development of Church's thought and indicate the principles transmitted by its teaching. From a methodological point of view, the authors refer to official texts in order to let the reader know the documents directly. Documents concerning nuclear energy and nuclear disarmament are not treated, as they would require a separate discussion.